Cardanol-based thermoset plastic reinforced by sponge gourd fibers (Luffa cylindrica) - Da Silva, André Leandro; Da Silva, Lucas Renan Rocha; De Andrade Camargo, Isabelle; Da Silva Agostini, Deuber Lincon [UNESP]; Dos Santos Rosa, Derval; De Oliveira, Diego Lomonaco Vasconcelos; Fechine, Pierre Basílio Almeida; Mazzetto, Selma Elaine (FapUNIFESP (SciELO), 2016)
A growing global trend for maximum use of natural resources through new processes and products has enhanced studies and exploration of renewable natural materials. In this study, cardanol, a component of the cashew nut shell liquid (CNSL), was used as a building block for the development of a thermosetting matrix, which was reinforced by raw and modified sponge gourd fibers (Luffa cylindrica). DSC and TG results showed that among biocomposites, the one reinforced by sponge gourd fibers treated with NaOH 10 wt% (BF10) had the highest thermal stability, besides the best performance in the Tensile testing, showing good incorporation, dispersion, and adhesion to polymer matrix, observed by SEM. After 80 days of simulated soil experiments, it has been discovered that the presence of treated fiber allowed better biodegradability behavior to biocomposites. The biobased thermoset plastic and biocomposites showed a good potential to several applications, such as manufacturing of articles for furniture and automotive industries, especially BF10.
Keywords: Biobased plastic; Biodegradable; Composites; Lignocellulosic fibers